The difference quotient and simplification will be = [4 -h-2x]
The given equation is as follows: f(x)= 4x - x²
For finding the quotient and further simplification we must follow the following steps:
[f(x + h) - f(x)] / h = [4(x + h) - (x + h)² - 4x + x²]/ h
<h3>What is simplification of algebraic operations?</h3>
Getting the functions in their lowest terms is known as simplification.
Brackets will get open and solved further;
[f(x + h) - f(x)] / h = [4(x + h) - (x + h)² - 4x + x²]/ h
[f(x + h) - f(x)] / h = [4h - h² - 2x]/ h
Finally dividing the whole equation with h;
= [4 - h - 2x]
Learn more about algebraic operations,
brainly.com/question/12485460
# SPJ1
16r^2+ 2r -4r
16r^2 - 2r
2r ( 8r -1)
Answer:
So, ![(a + b)^0=1](https://tex.z-dn.net/?f=%28a%20%2B%20b%29%5E0%3D1)
Step-by-step explanation:
![(a + b)^0](https://tex.z-dn.net/?f=%28a%20%2B%20b%29%5E0)
To evaluete this expression we apply exponential property
![x^0=1](https://tex.z-dn.net/?f=x%5E0%3D1)
IF any expression has exponent 0 then the value is 1 always
for example, ![3^0 =1](https://tex.z-dn.net/?f=3%5E0%20%3D1)
![5^0=1](https://tex.z-dn.net/?f=5%5E0%3D1)
because exponent is 0
So, ![(a + b)^0=1](https://tex.z-dn.net/?f=%28a%20%2B%20b%29%5E0%3D1)